Analysis of the water vapour sorption isotherms of oil palm trunk and rubberwood - Zaihan J; Hashim W S; Hill C A S; Mohd Dahlan J; Sun D Y (Journal of Tropical Forest Science, 2011)
Oil palm (Elaeis guineensis) trunk and rubberwood (Hevea brasiliensis) were studied to determine their sorption isotherm behaviours using a dynamic vapor sorption (DVS) apparatus. Oil palm trunk (OPT) was separated into six parts: two cross-sectional zones (inner and outer), vertical zones (top and bottom) and three types of tissues (parenchyma + vascular bundle, parenchyma and vascular bundle). The different parts of OPT and rubberwood showed differences in equilibrium moisture content (EMC) at each target relative humidity (RH) except for those from the top and bottom. The adsorption isotherms were analysed using the Hailwood-Horrobin (H-H) model and it was found to fit well with the experimental data. The dissolution water (Ms) and the projected fibre saturation point (p-FSP) in all parts of OPT were higher than in rubberwood. However, the values of hydration water (Mh) of all parts of OPT and rubberwood were similar. In the sorption hysteresis, rubberwood was higher than OPT. This could be related to differences in stiffness of the material. The sorption behaviour of the OPT material was affected by the presence of starch.
Keywords: Equilibrium moisture content; Hailwood-Horrobin; Rubber wood